Impact of the Childcare Physical Activity (PLAY) Policy on Young Children’s Physical Activity and Sedentary Time: A Pilot Clustered Randomized Controlled Trial - Szpunar, Monika (Int J Environ Res Public Health, 2021)
Background: The importance of daily physical activity is crucial for healthy development during the early years. Currently, a formal written physical activity policy is lacking in Canadian childcare centers, but holds promise for offering consistent physical activity opportunities. With eight recommendations, the Childcare PLAY policy is an evidence-informed, institutional-level document, targeting children’s physical activity, outdoor play, and sedentary time. The purpose of this study was to examine the impact of the Childcare Physical Activity (PLAY) policy on the physical activity and sedentary time of young children (18 months–4 years) in childcare. Methods: Nine childcare centers in London, Ontario participated in the cluster, randomized controlled trial. The centers in the control condition (n = 4) continued their typical daily routines, while the centers in the intervention condition (n = 5) implemented the PLAY policy for eight weeks. To assess physical activity levels, toddlers and preschoolers wore ActiGraph wGT3X-BT accelerometers for five consecutive days during childcare hours, at baseline, mid- and post-intervention, and at the six-month follow-up. Raw accelerometry data were converted to 15 s epochs, and age- and device-specific cut-points were applied. The participants with two or more days of at least 5 h/day of wear-time at baseline, and at one additional time point, were included in the linear mixed-effects models. An adjusted alpha (p < 0.017) was used to account for multiple comparison bias. Results: A total of 148 children (31.92 ± 7.41 months) had valid accelerometry data. The intervention resulted in a significant increase in light physical activity among the participants in the experimental group at the six-month follow-up (+1.07 min/h, an 11.16% increase; p = 0.0017). The intervention did not have a statistically significant effect on the total physical activity, moderate-to-vigorous physical activity, or sedentary time. Conclusions: The findings indicate that the Childcare PLAY policy was effective at increasing the toddlers’ and preschoolers’ light physical activity. This pilot intervention appears promising for supporting some improved movement behaviors among children in childcare settings; however, additional investigations are needed to explore the feasibility and effectiveness with larger and more-diverse samples.